2019
DOI: 10.6061/clinics/2019/e1218
|View full text |Cite
|
Sign up to set email alerts
|

Secondary healing strategy for difficult wound closure in invasive vulvar cancer: a pilot case-control study

Abstract: OBJECTIVES: Despite the number of surgical advances and innovations in techniques over time, radical vulvectomy frequently results in substantial loss of tissue that cannot be primarily closed without tension, the mobilization of surrounding tissues or even the rotation of myocutaneous flaps. The aim of this study was to evaluate the feasibility of leaving the surgical vulvar open wound for secondary healing in situations where primary closure of the vulvar wound is not possible. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Local fasciocutaneous flaps are usually the first choice of many surgeons in the absence of extensive tissue deficiency (2,7). Successful results have even been reported by leaving primary non-closable defects to secondary healing (11). The blood circulation of the perineal area, gluteal region and medial part of the thigh is provided by a rich perforator vascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local fasciocutaneous flaps are usually the first choice of many surgeons in the absence of extensive tissue deficiency (2,7). Successful results have even been reported by leaving primary non-closable defects to secondary healing (11). The blood circulation of the perineal area, gluteal region and medial part of the thigh is provided by a rich perforator vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in the reconstruction of vulva and perineum defects; emerges as another disadvantage. Increased body mass index and obesity are important negative factors in the development of wound complications (11,17). In our study, body mass index was 34.8±3.5 (32.2-39.0) kg/m 2 in patients with wound complications; determination of body mass index as 26.5±1.7 (24.1-30.1) kg/m 2 in patients without wound complications supports these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is usually the first choice for patients with earlystage vulvar SCC, including radical vulvectomy with bilateral inguinofemoral lymphadenectomy as a treatment of choice for vulvar SCC; 19 however, the substantial loss of tissue involved in such surgery results in a risk of postoperative complications. 20 After consultation with several hospitals, it was concluded that surgery and chemotherapy would be intolerable for our patient, because of her history of AA. In this case, radiotherapy was the only option.…”
Section: Dovepressmentioning
confidence: 91%
“…Evidence also suggests the beneficial role of CAP in the acceleration of healing different wounds without side-effects (i.e., premalignant lesions). As a result, CAP is an appropriate clinical approach for the treatment of wounds after surgical intervention, mostly for minimizing prolonged wound healing, which is associated with a poor prognosis due to delayed adjuvant therapy [198].…”
Section: Plasma Promoted Wound Healing and Its Possibilities In The Smentioning
confidence: 99%